The Impact of General Self-Efficacy on Psychological Resilience During the COVID-19 Pandemic: The Mediating Role of Posttraumatic Growth and the Moderating Role of Deliberate Rumination - Zeng, Wei; Wu, Xingrou; Xu, Yanhua; Wu, Jiamin; Zeng, Yuqing; Shao, Jinlian; Huang, Dongtao; Zhu, Ziqi (Frontiers in Psychology, 2021)
Purpose: This study used a moderated mediation model to explore the relationship between general self-efficacy (GSE) and psychological resilience (PR) and the associated mechanisms, the mediating role of post-traumatic growth (PTG) and the moderating role of deliberate rumination (DR) during the COVID-19 pandemic. Methods: The college students who participated in this study came from an independent college in Guangdong Province, China. A total of 918 college students completed the survey, and the final data sample size was 881. SPSS 23.0 and PROCESS (version 3.3) were used to conduct Pearson correlation analysis and hierarchical regression linear analysis on the data. Results: (1) The correlation analysis showed that GSE and PR are positively correlated, and that PTG is positively correlated with GSE and PR. DR is positively correlated with GSE, PTG and PR. (2) The results of mediation analysis showed that GSE has a direct predictive effect on DR, and PTG partially mediates the relationship between the two. (3) The results of moderating-effect analysis showed that DR hinders the effect of GSE on PTG but enhances the positive impact of PTG on PR. Conclusions: GSE can improve PR under the mediating influence of PTG. DR played a positive moderating role in the relationship between GSE and PTG, and played a negative moderating in the relationship between PTG and PR. These results advance the understanding of the mechanism between GSE and PR.